Timing of eye removal influences low-vision quality of life and self-perception of facial appearance in people with one eye. - Aysha N Kinakool; Stefania S Moro; Jennifer K E Steeves (PLoS ONE)
Purpose The loss of one eye early compared to late in life coincides with critical periods of postnatal visual development and is associated with sensory adaptations which may lead to different psychosocial experiences throughout life. This study investigates the impact of age at enucleation on psychosocial health factors, namely low-vision quality of life, self-perception of facial appearance, anxiety, and depression. Methods Twenty-two participants with early or late eye removal and twenty-seven binocular viewing controls completed the Low-Vision Quality of Life questionnaire, Facial Appearance sub-scale of the Negative Physical Self-Scale and the Hospital Anxiety and Depression scale. Results Low-vision quality of life was lower for people who had their eye removed late in life compared to binocular viewing controls. Further, within this group, lower self-perception of facial appearance was associated with lower low-vision quality of life. Moreover, experience with binocularity and time since enucleation were not associated with psychosocial health factors. Conclusion Developmental factors rather than experiential factors appear to influence psychosocial health since binocular experience and time since enucleation were not related to any psychosocial factor. These findings suggest that people who have had their eye removed early in life, during the critical periods of visual development may benefit from better psychosocial outcomes.